Avaliação do efeito dos resultados do SPAECE em língua portuguesa dos alunos do 5º e 9º ano na visão de docentes do município de Aracati/CE - Costa, Artemízia Ribeiro Lima (2018)
Evaluations, on a large scale, are intended to provide information about the education development in general; through the students’ performance evaluation, in this research, it was intended to focus the study on the tests applied in elementary education. The information generated should serve as a subsidy, not only for educational managers from the governmental spheres, but also as a tool to guide pedagogical actions in schools, since teachers' perspective on this subject is the main point of this investigation. This study aims to analyze the effects of the SPAECE learning results in the 5th and 9th grade in Portuguese Language from teacher’s perspective, in the city of Aracati / CE. The methodological procedures included bibliographic research of important authors in educational evaluation and in teaching of Portuguese Language, as well as documentary analysis (Federal, State and Municipal spheres) connected to learning. In the field research, a questionnaire composed of objective and subjective questions was used, which were quantitatively and qualitatively analyzed. In the quantitative aspect, the Statistical Parsing of Social Science (SPSS) program was used for Factorial and Regression Analysis; connected to the qualitative aspect, this one had as reference for the analyzes, Bardin (2009) approaching the Analysis of the Content. The results show the teaching experience, since all of them have a degree in the area or in related areas, being only one out of area, and still a large part claim to attend to a expertise course in the area. About employment relationship, 75% have a temporary bond, which demonstrates the fragility of the system, since this functional situation may contribute negatively to possible continuing education actions. It was found that there is a strong positive view, on the part of the respondents, to relate the SPAECE with its teaching practice for the improvement of learning, being pointed as significant to the SPAECE results and the information flow in the many places: secretary, school and classroom. In the teachers’ perspective, the SPAECE addresses references about the pedagogical work, implying to review actions in the classroom, inviting them rethink methodologies adopted, looking for students’ skills and abilities development.